2010
DOI: 10.1111/j.1365-2850.2010.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Description and evaluation of a serious game intervention to engage low secure service users with serious mental illness in the design and refurbishment of their environment

Abstract: Service user involvement in all levels of healthcare provision is the expectation of UK government policy. Involvement should not only include participation in the planning and delivery of health care but also the exercise of choice and opinions about that care. In practice, however, service user engagement is most often tokenistic, involving post hoc consultation over plans already committed to by services. This paper explores an Occupational Therapy-led initiative to use the Serious Game format to engage low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Of those that evaluated experiences, ten studies reported positive views, while in two studies, patients reported negative experiences and two studies reported both positive and negative experiences (Additional file 3 : Table S1). Of the positive experiences, patients and carers expressed satisfaction with the engagement processes [ 43 , 78 ] were interested in continuing their involvement in the longer term, [ 75 ] felt the experience to be educational, [ 52 ] and felt that participation highlighted issues that would have otherwise been ignored [ 39 , 64 , 75 ]. Positive experiences were linked to feeling empowered and independent as a result of skills development and positive recognition [ 58 , 59 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of those that evaluated experiences, ten studies reported positive views, while in two studies, patients reported negative experiences and two studies reported both positive and negative experiences (Additional file 3 : Table S1). Of the positive experiences, patients and carers expressed satisfaction with the engagement processes [ 43 , 78 ] were interested in continuing their involvement in the longer term, [ 75 ] felt the experience to be educational, [ 52 ] and felt that participation highlighted issues that would have otherwise been ignored [ 39 , 64 , 75 ]. Positive experiences were linked to feeling empowered and independent as a result of skills development and positive recognition [ 58 , 59 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some successes in more intense participation came through engagement processes built into interactions between patients and practitioners, particularly in community-based services with recurring interaction with patients [ 28 – 31 ]. In these processes, there were no additional costs to attending an engagement event beyond seeking care and patients could directly benefit from changes to services.…”
Section: Resultsmentioning
confidence: 99%
“…Most projects, particularly those involving more intense levels of engagement, engaged participants on issues related to a specific health service. Participants were recruited from the service and patients were motivated to participate because they had opportunity to directly impact these services and therefore their own lives [ 21 , 26 , 28 – 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only has this led to improved patient experiences and reduced aggression towards frontline staff [ 53 ], but also project evaluations report ÂŁ3 worth of benefits for every ÂŁ1 spent [ 54 ]. Involving patients directly in the redesign and refurbishment of low-secure mental health units, using a ‘serious gaming’ approach, has also provided valuable insight into the needs of otherwise difficult-to-engage groups and has led to practical service improvements [ 55 ].…”
Section: Design-led Person-centred and Multilevel Interventions In Tmentioning
confidence: 99%